Bone mineral density, bone metabolism‐related factors, and microRNA‐218 are correlated with disease activities in Chinese ankylosing spondylitis patients. Issue 2 (4th January 2022) - Liu, Jiayan; Zhao, Li; Yang, Xue; Liu, Congjin; Kong, Ning; Yu, Yiyun; Xuan, Dandan; Wan, Weiguo; Xue, Yu
Abstract: Objective: To investigate bone mineral density (BMD), bone metabolism‐related factors, and microRNA‐218 in Chinese ankylosing spondylitis (AS) patients and to identify their correlation with disease activities and the treatment with TNF‐α inhibitors. Methods: A total of 89 AS patients were enrolled in the study. Patients' information and laboratory examination results were collected. BMD of the anteroposterior lumbar spine (L2‐L4), left femoral neck, and whole body were measured and T‐scores were calculated. MicroRNA‐218 was extracted from PBMCs of AS patients and detected by RT‐PCR. Bone metabolism‐related factors were detected using protein chips and flow cytometer. Results: Out of 86 patients undergoing whole‐body BMD measurement, 14 had osteopenia and 72 had normal BMD without osteoporosis or high BMD. Compared with short‐ (disease duration ≤3 years) and long‐term groups (disease duration ≥10 years), medium‐term group (disease duration ranges from 3 to 10 years) showed lowest BMD. Patients with onset age ≤20 years old had significantly lower BMD than the other groups ( p  < 0.05). The BMD of femoral neck had negative correlation with CRP ( p  < 0.05) and no correlation with BASDAI or ESR. Both whole‐body BMD and femoral neck BMD were negatively correlated with BASMI ( p  < 0.05). Dickkopf‐1 (DKK‐1), platelet‐derived growth factor‐BB (PDGF‐BB), and receptor activator of NF‐κB ligand (RANKL)/osteoprotegerin (OPG) were significantly increased, while Osteopontin (OPN) was significantly decreased in AS patients. Expression of microRNA‐218 in PBMC of AS patients was low and was positively correlated with BASMI ( p  < 0.05), but it was not correlated with the duration of disease, age of onset, BASDAI, ESR, or BMD. Conclusion: Loss of bone mass mainly occurred at the inflammatory sites in AS patients, depending on the severity of inflammation. The alleviation of inflammation can improve loss of bone mass and bone metabolism disorders. Anti‐inflammatory treatment is critical for the treatment of secondary osteoporosis caused by AS. Abstract : Figure 1 A One patient of osteopenia detected by whole‐body DXA. B One patient of osteoporosis in lumbar vertebrae by DXA showing visible joint space and osteoporosis. C One patient of high BMD in lumbar vertebrae by DXA showing visible articular surface fusion. D One patient of normal BMD in lumbar vertebrae with clear joint space.